The development of the Irish census, and its national importance - Thompson, William J. (Statistical and Social Inquiry Society of Ireland, 1912)
The people of Great Britain and Ireland are accustomed every ten years to the taking of the Census, occurring, as it does, in the first year of each decennial period. To a majority of the population this may seem a comparatively routine business, and to many, no doubt, a great trouble, as the head of each family is required to give certain information by means of a Form which must be filled up on a specified day. The information received, however, from this Form, troublesome as it may have appeared to some individuals to give, is of the greatest importance from a social, statistical, and national point of view.
Read Wednesday, the 15th March, 1911.
Keywords: Census; Demographics; 314.15